Pengaruh Pemanfaatan Platform Video Pembelajaran dan Motivasi Belajar terhadap Hasil Belajar PAI Siswa Kelas VIII SMP Ma’arif NU Karanggedang - Annisa Nur Baeti; Ifada Novikasari (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to examine the influence of the utilization of learning video platforms and students' learning motivation on the learning outcomes of eighth-grade students at SMP Ma’arif NU Karanggedang. This research employed a quantitative correlational approach involving 40 students as the research sample. Data were collected using a four-point Likert scale questionnaire. The data were analyzed through descriptive statistics, reliability testing, normality testing, and multiple linear regression analysis using Jamovi software. The findings indicate that the utilization of learning video platforms and students' learning motivation have a positive and significant effect on the learning outcomes of eighth-grade students. This is evidenced by a significance value of 0.001 (< 0.05) and a regression coefficient of 0.936. Furthermore, the coefficient of determination (R²) of 0.593 indicates that the utilization of learning video platforms and learning motivation account for 59.3% of the variance in students' Islamic Religious Education (PAI) learning outcomes, while the remaining 40.7% is explained by other factors beyond the scope of this study. Therefore, the effective utilization of learning video platforms, accompanied by strong learning motivation, can contribute to improving students' learning outcomes in Islamic Religious Education when appropriately integrated into the teaching and learning process.   Keywords: Learning Video Platforms; Learning Motivation; Learning Outcomes; Junior High School